Preventive Effect of Antioxidant From Purple Rosella Yoghurt on Duodenum and Colon Histopathology of Rattus norvegicus Exposed to Rhodamine B And Saccharin - Haskito, Ajeng Erika Prihastuti; Nariswari, Bintari; Safitri, Anna; Noviatri, Aldila; Untari, Handayu; Sari, Citra (The Journal of Experimental Life Science, 2024)
Rodhamine B and Saccharin are often misused by food producers as food additive, which, if their use is not monitored, can produce free radicals that cause oxidative stress conditions in the body, leading to dangerous damage to the body. The addition of purple rosella in yoghurt can increase the functional value of the yoghurt, namely increasing the antioxidant content. The purpose of this study was to determine the benefits of giving purple rosella yoghurt in preventing damage to the duodenum and colon of (Rattus norvegicus) caused by Rodhamine B and Saccharin. This study used Completely Randomized Design (CRD) with 28 male R. novergicus, Wistar strain in aged 8-12 weeks. Group K was not given any treatment; R was given Rodhamine B, S was given Saccharin, KRS was given Rodhamine B and Saccharin, YR was given Rodhamine B and yoghurt, YS was given Saccharin and yogurt, YRS was given Rodhamine B, Saccharin and yogurt. The dose of Rodhamine B was 22.5 mg.kg-1, Saccharin was 157.77 mg.kg-1, and the volume of yoghurt was 1 mL.head-1. They were administered orally with a gastric tube for 14 days. The concentration of purple rosella extract added to yoghurt was 15% (v/v). Parameters were observed in histopathology of the duodenum and colon with the scoring method. Data analysis was done with the Kruskal-Wallis test followed by the Mann-Whitney test. The KRS group showed the heaviest damage, namely necrosis, villi erosion, and inflammatory cell infiltration of >75% of the total visual field in the duodenum and colon. The YR, YS, and YRS groups showed significant changes compared to the R, S, and KRS groups, namely necrosis, villous erosion, and inflammatory cell infiltration, which appeared to be 25-50% of the total visual field. However, this did not match the condition of group K, which appeared to be <25% of the total visual field. The provision of purple rosella yoghurt can prevent 50% damage to the duodenum and colon of Rattus novergicus due to Rodhamine B and Saccharin. Keywords: colon, duodenum, Rodhamine B, Saccharin, yoghurt.